Siła „jedynek” w wyborach do Sejmu RP - Pastorczyk, Wioleta (Polityka i Społeczeństwo, 2021)
The aim of the article was to investigate whether the order of the candidates on the party lists has any significance and influence on the result of the election. The analysis is based upon the results of voting on regional lists four major political parties from the last four elections to the Parliament. The research found that the vast majority of voters vote for the leaders of the lists, regardless of the political options supported. If the candidate is placed lower on the list, he will get less votes from the Polish electorate. Therefore it was demonstrat-ed that the position of the candidate clearly determines his success in the elections. It was also observed that the chance of getting the mandate is dependent not only on the place occupied by the candidate, but also the percentage of support for the political party that he represents. It is important to note that the leaders of the party don’t get always the most votes from their list and not every ‘number one’ becomes a member of parliament.